Penggunaan Energi Terbarukan PLTS untuk Efisiensi Biaya dan Keberlanjutan Usaha Bubur Bayi Shashi di Bukittinggi - Dedi Tri Laksono; Nofri Dodi; Rien Afrianti; Rajimar Suhal Hasibuan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Shashi Baby Porridge business in Bukittinggi faces significant operational cost challenges due to high electricity consumption, particularly from production equipment. To address this issue, a community service team from the Department of Electrical Engineering at Padang State Polytechnic implemented a Solar Power System (SPS) as an alternative solution. The service process included energy needs analysis, SPS system design, installation, and performance monitoring and evaluation. The implementation of the SPS successfully reduced electricity costs and dependence on conventional electricity while supporting environmental conservation efforts. The installed SPS, with a total capacity of 200 Wp, provides energy for lighting, resulting in significant savings in operational costs. Socialization with the owners and workers was also carried out to ensure optimal system maintenance and operation. The outcomes of this project are expected to inspire other small businesses to adopt renewable energy technologies to enhance efficiency and sustainability.